Digital Skill Trainin for Deaf Community in Sorong City - Aras, Suhardi; Yusuf, Muhammad; Surahmanto, Muhammad; Pangri, Muzakkir (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2024)
This community service program aims to make a direct contribution to the community. The main focus is to enhance participants' understanding of the application of artificial intelligence (AI) to support learning and earn income through micro-job services on various platforms. There were 40 participants in this activity, which was held in person on November 9, 2024 at Hangout Avenue, Sorong City. The methods used included the delivery of materials through lectures, question and answer sessions, and hands-on training in the use of AI applications and micro-job services. The results showed a significant increase in participants' understanding and skills in the use of digital technology to support the economy and education. This program has an important role in the empowerment of the Deaf community, students, and college students so that they can make the best use of emerging AI applications to complete microjobs on various platforms and increase their income